AUDITING PROCESS ON ELECTRONIC COMMERCE SYSTEMS - Wali Saputra (Akuntabilitas, 2016)
Issues concerning electronic commerce are increasing as more companies are developing a web presence and conducting business on the Internet.The technological and economic development of the latest centuries resulted in the significant development of the electronic commerce, and the changes made in the manner of executing transactions had important repercussions on the manner of executing the audit.  Electronic commerce has rapidly transformed the way auditing functions are performed, posing challenges to the auditing profession. A few guidelines exist for meeting some of these  challenges.The purpose of our paper  is  to explain about how to undertake audit process on electronic commerce systems. This paper presents information systems auditing, electronic commerce and the stages of audit process which should be conducted by auditors in case of companies that use electronic commerce system and the manner in which these combine with the audit in the classic environment of transactions.DOI: 10.15408/akt.v9i1.3581